2013
DOI: 10.1186/1479-5876-11-135
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose temozolomide before dendritic-cell vaccination reduces (specifically) CD4+CD25++Foxp3+ regulatory T-cells in advanced melanoma patients

Abstract: BackgroundIn cancer immunotherapy, dendritic cells (DCs) play a fundamental role in the dialog between innate and adaptive immune response, but several immunosuppressive mechanisms remain to be overcome. For example, a high number of CD4+CD25++Foxp3+ regulatory T-cells (Foxp3+Tregs) have been observed in the peripheral blood and tumor microenvironment of cancer patients. On the basis of this, we conducted a study on DC-based vaccination in advanced melanoma, adding low-dose temozolomide to obtain lymphodepleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…For this purpose, several therapeutic approaches that use small Reduces the number of Tregs [121] molecule inhibitors, antibodies or phytochemicals that specifically target molecules and signaling pathways involved in the recruitment, activation and function of tumor infiltrating non-malignant cells have been tested in both animal models and human. Table 1 summarizes the most up-to-date drugs available with potential use in cancer therapy, known effects on tumor cells and activity against tumor-stromal microenvironment communications.…”
Section: Molecular Network In the Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, several therapeutic approaches that use small Reduces the number of Tregs [121] molecule inhibitors, antibodies or phytochemicals that specifically target molecules and signaling pathways involved in the recruitment, activation and function of tumor infiltrating non-malignant cells have been tested in both animal models and human. Table 1 summarizes the most up-to-date drugs available with potential use in cancer therapy, known effects on tumor cells and activity against tumor-stromal microenvironment communications.…”
Section: Molecular Network In the Tumor Microenvironmentmentioning
confidence: 99%
“…Finally sclareol and temozolomide reduce tumor growth and the number of tumor infiltrating Tregs [120,121]. Therefore, although further studies will be needed to determine which cell(s) is/are the best therapeutic target(s) and which drugs are the most efficient and selective, there is no doubt that the therapeutic targeting of tumor microenvironment cells represents a valuable strategy to complement conventional anticancer strategies.…”
Section: Molecular Network In the Tumor Microenvironmentmentioning
confidence: 99%
“…[8][9][10]57 To improve clinical efficacy, it is probably necessary to combine vaccination with checkpoint modulators or other strategies countering immunological tolerance. 6,25,52,[66][67][68][69][70][71] As a combination strategy will increase the risk of side effects, it is encouraging that our vaccine study indicated low toxicity, even after long-term follow-up. One may further note that the longterm survivors (M22 and M109) responded well to treatment with ipilimumab.…”
Section: Discussionmentioning
confidence: 82%
“…By depleting the immune cells, these drugs eliminate negative regulators such Tregs and MDSCs, promoting a favorable environment for DC-induced expansion of antitumor effector cells in the recovery phase. In a pilot clinical trial, Ridolfi et al 161 showed that the administration of low doses of temozolomide to melanoma patients before DC vaccination specifically reduced the CD4 1 CD25 1 Foxp3 1 Tregs. In turn, cyclophosphamide was shown to enhance antitumor immunity through mechanisms that rely on Treg elimination and resetting DC homeostasis.…”
Section: Q31mentioning
confidence: 98%